2020
DOI: 10.1007/s10803-020-04638-6
|View full text |Cite
|
Sign up to set email alerts
|

‘I Felt Like I was Floating in Space’: Autistic Adults’ Experiences of Low Mood and Depression

Abstract: It is recognised that a high proportion of adults on the autism spectrum experience depressive symptoms. However, limited research has explored autistic peoples’ experiences of low mood and depression. The aim of this study was to explore the lived experiences of low mood and depression for adults on the autism spectrum. The study employed Interpretive Phenomenological Analysis to investigate the experiences of 8 adults (7 males and 1 female), aged between 19 and 51, who had a diagnosis of autism without co-oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Since then, qualitative studies on autistic adults have become more expansive, covering themes such as friendships and relationships (Sala et al, 2020 ; Sosnowy et al, 2019 ), the diagnostic process (Huang et al, 2020a ; Mason et al, 2019 ), coping strategies (Ghanouni & Quirke, 2022 ; Hull et al, 2017 ), and gender related challenges and experiences (Coleman-Smith et al, 2020 ; Milner et al, 2019 ). Only one qualitative study on autistic adults directly addressed negative mood (Jordan et al, 2021 ), and specifically focused on how adults experienced low mood and depression. No study to date has directly surveyed autistic adults on specific experiences as a source of their emotional states.…”
mentioning
confidence: 99%
“…Since then, qualitative studies on autistic adults have become more expansive, covering themes such as friendships and relationships (Sala et al, 2020 ; Sosnowy et al, 2019 ), the diagnostic process (Huang et al, 2020a ; Mason et al, 2019 ), coping strategies (Ghanouni & Quirke, 2022 ; Hull et al, 2017 ), and gender related challenges and experiences (Coleman-Smith et al, 2020 ; Milner et al, 2019 ). Only one qualitative study on autistic adults directly addressed negative mood (Jordan et al, 2021 ), and specifically focused on how adults experienced low mood and depression. No study to date has directly surveyed autistic adults on specific experiences as a source of their emotional states.…”
mentioning
confidence: 99%
“…Prior research in non-autistic populations suggests that negative self-related beliefs may increase the risk of undesirable outcomes from repetitive thinking, especially when that repetition is negatively focused (Watkins, 2008). Other researchers have also suggested that autistic individuals may engage in more rumination related to mistakes or rejection in social spheres, perhaps particularly tied to a sense of not-belonging and rejection sensitivity (Jordan et al, 2020;Keenan et al, 2018). Notably, the RRS nodes considered most central in the current study only partially overlapped with those reported in a previous study of the measure's network structure (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Negative thoughts about the self (ie, not fitting in), feeling disconnected/isolated from oneself and others, physiological symptoms, and shame have also been cited. 9,26,27 Participants in one study reported camouflaging symptoms and emotions to fit in, which may be common among individuals with ASD and without ID, putting additional strain on their mental health as well as complicating diagnosis. 26 However, these studies are small, and larger systematic studies are necessary to establish a model of depression in adults with ASD.…”
Section: Resultsmentioning
confidence: 99%